The voiceless generation - Vanessa Malila (Communicare)
Nyamnjoh (2005:1) argues that “… the media … can, in principle, facilitate popular empowerment as a societal project”. The problem is that the news media do not seem to be doing this for young people in South Africa. This paper provides an analysis of selected news media and their representation of young people through coverage of the education sector in South Africa. The aim is to examine whether the media are fulfilling two key functions in their role as facilitators of popular empowerment in the public sphere: Do they provide citizens with the information they require to engage in issues that affect them (such as education), and secondly, do the media provide a space for citizens to voice their concerns and debates about those issues? A content analysis of print and online media provides an overview of the kind of coverage young people are exposed in reports on education. On the strength of the evidence thus acquired, this paper argues that the news media are failing to enable young people to be active citizens because they do not provide information that engages the youth in respect of education coverage and, when they do cover education, the reports do not feature the voices of young people.